2023
DOI: 10.1101/2023.10.25.563997
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The prevalence ofFusobacterium nucleatumsubspecies in the oral cavity stratifies by local health status

Madeline Krieger,
Yasser M. AbdelRahman,
Dongseok Choi
et al.

Abstract: The ubiquitous inflammophilic pathobiont Fusobacterium nucleatum is widely recognized for its strong association with a variety of human dysbiotic diseases such as periodontitis and oral/extraoral abscesses, as well as multiple types of cancer. F. nucleatum is currently subdivided into four subspecies: F. nucleatum subspecies nucleatum (Fn. nucleatum), animalis (Fn. animalis), polymorphum (Fn. polymorphum), and vincentii/fusiforme (Fn. vincentii). Although these subspecies have been historically considered as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…who recently reported that in healthy dental plaque, F. nucleatum subsp. polymorphum is the dominant subspecies, followed by subspecies animalis and vincentii [5]. Eren et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…who recently reported that in healthy dental plaque, F. nucleatum subsp. polymorphum is the dominant subspecies, followed by subspecies animalis and vincentii [5]. Eren et al .…”
Section: Discussionmentioning
confidence: 99%
“…This distribution is similar to that described by Krieger et al who recently reported that in healthy dental plaque, F. nucleatum subsp. polymorphum is the dominant subspecies, followed by subspecies animalis and vincentii [5]. Eren et al also reported that F. nucleatum subsp.…”
Section: Analysis Of Adhesion Phenotypesmentioning
confidence: 97%
See 1 more Smart Citation